2004
DOI: 10.1093/treephys/24.6.689
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of leaf conductance and water potential of five Himalayan tree species

Abstract: We studied variations in water relations and drought response in five Himalayan tree species (Schima wallichii (DC.) Korth. (chilaune) and Castanopsis indica (Roxb.) Miq. (dhale katus) at an elevation of 1400 m, Quercus lanata Smith (banjh) and Rhododendron arboreum Smith (lali gurans) at 2020 m, and Quercus semecarpifolia Smith (khasru) at 2130 m) at Phulchowki Hill, Kathmandu, Nepal. Soil water potential at 15 (Psi(s15)) and 30 cm (Psi(s30)) depths, tree water potential at predawn (Psi(pd)) and midday (Psi(m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…It is also possible that redistribution of water stored in roots of trees may help in raising the water potential of shoots. Poudyal et al (2004) observed a decrease in wood water content before the onset of leaf flushing, that suggests withdrawal of stored stem water during active phenological development, which may contribute to rehydration of active tissues (Borchert 1994). The establishment of new foliage shortly before the warm and wet rainy season is likely to optimize photosynthetic gain .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is also possible that redistribution of water stored in roots of trees may help in raising the water potential of shoots. Poudyal et al (2004) observed a decrease in wood water content before the onset of leaf flushing, that suggests withdrawal of stored stem water during active phenological development, which may contribute to rehydration of active tissues (Borchert 1994). The establishment of new foliage shortly before the warm and wet rainy season is likely to optimize photosynthetic gain .…”
Section: Discussionmentioning
confidence: 92%
“…Zobel et al (2001) found lowest water potential at high elevations in this region. Poudyal et al (2004) studied water relations and drought response in five dominant forest tree species in Nepal and found significant variation among sites, species and season in predawn and midday water potential and monthly soil water potential at 15 cm depth for all species. In a subtropical savanna, Nelson et al (2002) found that DS were more deterministic and constrained in their growth responses to increased moisture availability than ES.…”
Section: Introductionmentioning
confidence: 99%
“…In an artificial watering experiment in Tabebwa ochracea, a tropical tree species, flower buds' size increased within 2 days of watering and were in full bloom after 5-7 days (Borchert 1994b). Some tree species are able to rehydrate active tissues before leaf flushing by withdrawing stored stem water (Poudyal et al 2004). Significant increase in soil moisture percentage after precipitation is quite obvious and consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Water relations of these forests have been investigated by Zobel & Singh (1995), Tewari (1998), Zobel et al (2001, Poudyal et al (2004) and Singh et al (2006), while their phenology was studied by Ralhan et al (1985), Pangtey et al (1990), Rawal et al (1991) and Negi (2006). Rhododendrons (Ericaceae) are under-canopy forest tree species widely distributed around the globe.…”
Section: Introductionmentioning
confidence: 99%
“…There is little information regarding the role of water in controlling leaf phenology of temperate trees especially central Himalayan trees. Most evergreen tree leaves in the central Himalaya have a life span of more than one year, a period longer than for deciduous leaves [11][12][13] . Phenological processes such as leaf emergence, expansion, flowering and fruiting occur before the onset of monsoon when trees still bear old leaves unlike in deciduous trees where rehydration of leafless twigs becomes a prerequisite for initiation of new leaves 3,14,15 and the loss of leaf dynamics (nitrogen, specific leaf mass, etc.)…”
Section: Introductionmentioning
confidence: 99%